The Effect of Conformity and Emotional Intelligence on the Aggressiveness of Civil Service Police Unit (Satpol PP) Members in Padang City - Genta Prasetya; Mario Pratama (Darul Yasin Al Sys, 2026)
Although aggressive behavior among law enforcement personnel has received considerable scholarly attention, limited research has examined the combined influence of conformity and emotional intelligence on members of Indonesia’s Civil Service Police Unit (Satpol PP). This study analyzes the effects of conformity and emotional intelligence on aggressive behavior among Satpol PP members in Padang City. A quantitative correlational design was employed, involving 186 respondents selected through purposive sampling. Data were collected using the Conformity Scale, the Wong and Law Emotional Intelligence Scale, and the Aggression Questionnaire and analyzed through multiple linear regression. The findings demonstrate that emotional intelligence has a significant negative effect on aggressive behavior, whereas conformity has a significant positive effect. Collectively, the two predictors explain 28.9% of the variance in aggressive behavior. These results indicate that stronger emotional intelligence may reduce aggressive responses, while conformity to group norms may increase such behavior during public-order enforcement. The study concludes that cultivating constructive group solidarity and strengthening emotional intelligence are essential for mitigating aggressive responses in high-pressure field operations. The findings extend social psychological understanding of emotion regulation and group dynamics among law enforcement personnel and provide practical implications for government institutions seeking to develop more humane standard operating procedures and implement emotional intelligence training. Further research may employ qualitative approaches or examine mediating variables to provide a more comprehensive explanation of aggressive behavior among law enforcement officers.